Qualitative characteristics of accounting information in the belief revision of the users for the securities prospects in Indonesia Stock Exchange (IDX) - MF. Arrozi Adhikara; Maslichah Maslichah; Nur Diana (Universitas Hayam Wuruk Perbanas, 2014)
The research attempts to reveal, in explanatory causality, the effect of the use of ac- counting information on the belief revision of stock selection for the security prospects in Indonesia Stock Exchange. The data were collected using survey on investment managers with individual unit analysis, through simple random sampling. They were analyzed using structural equation model (SEM). The result shows that there is posi- tive effect of the usefulness of accounting information on belief revision and return preferences; there is positive effect of the usefull of price information on belief revision and return preferences; there is positive effect of systematis risk on the usefulness of price information, and there is positive effect of belief revision on return preferences. This result also indicates negative effect of the usefulness of accounting information on the unsystematic risk; the negative effect of systematic risk on belief revision, as well as the negative effect of unsystematic risk on belief revision. Variables of unsystematic risk and belief revision are a mediating variable because it is increasing the effect and the relationships among variables. Yet, the use of price information is as a mediating because it lowers the effect between variables.The study also shows that accounting information is very useful because it contains value, relevan, reliabel, comparative information and has prospect in the future in decision making. Investment managers shlod be sophisticated, rational, prudent, and have risk preferences that can make a positive contribution in the advisory to investors.